(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In the article, information on the milk yield of Estonian red cows of different production types is covered. Cows fed and kept under the same conditions on the farm showed different milk productivity during lactation in the cross-section of production types. Cows in experimental group II (type of milk production) gave 400 kg or 10.2 percent more milk during lactation than cows in control group I. In terms of 4% fat milk obtained during lactation, experimental group II was superior to cows of control group I by 370.7 kg units (**P>0.99). When the indicators of milk fat and protein output of cows are compared, the cows of group II have higher milk fat output. I was superior to the control group by 14.8 kg and milk protein output by 9.8 kg (**P>0.99).